Telaah Kritis terhadap Pemikiran al-Juwayni tentang Wahdaniyyah dan Risalah - Khalil Al-Farahidy; Aris Fauzan; Mohammad Syifa Amin Wigdodo (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2022)
Wahdaniyyah and prophethood are two things that must be believed to be valid until the end of time for every human being. These two things will continue to exist in the minds of humans and will not be erased. As for the Shari'a, it is different from the prior in that there will come a time when people will forget about it. When this period comes, humans will not be remorseful about departing from the Shari'a unless they leave these two things. This is the thought of Imam al-Haramain al-Juwayni, a scholar from the Shafiʻiy school, written in one of his books: Ghiyath al-Umam fi iltiyath al-Zulam. This thought is in line with a hadith which states that knowledge will be uprooted from the earth's surface with the scholars' death. The meaning of wahdaniyyah is a form of acknowledgment of the Almighty God. At the same time, prophethood is the sending of messengers by God Almighty to give instructions to humans about His authority.   Abstrak: Wahdaniyyah dan risalah merupakan dua hal yang mutlak untuk diyakini kebenarannya sampai akhir zaman bagi setiap manusia.  Kedua hal ini akan terus ada di benak manusia dan tidak akan terhapus selamanya.  Adapun syariat yang lain berbeda dengan kedua hal tersebut, yang mana akan datang suatu masa manusia akan lupa terhadapnya. Dan jika masa ini datang, manusia tidak bedosa dengan sebab meninggalkan syariat, kecuali jika mereka meninggalkan dua hal tersebut.  Inilah pemikiran dari Imam al-Haramain al-Juwayni, seorang ulama dari madhhab Shafiʻiy, yang dituliskan dalam salah satu bukunya: Ghiyath al-Umam fi iltiyath al-Zulam.  Pemikiran ini selaras dengan sebuah hadits yang menyatakan bahwa ilmu akan dicabut dari muka bumi dengan meninggalnya para ulama. Maksud dari wahdaniyyah adalah bentuk pengesaan kepada Rabb Yang Maha Esa.  Sedangkan risalah adalah pengutusan rasul oleh Tuhan Yang Maha Esa untuk memberi petunjuk kepada manusia tentang pengesaan.